Analysis of the Associated Factors of Doctor Job Satisfaction at Covid-19 Pandemic - Rendi Deva Andra; Ratni Prima Lita; Adila Kasni Astiena (University of Merdeka Malang, 2022)
The Covid-19 pandemic has caused doctors to have lower job satisfaction compared to the previous period. Preliminary survey conducted at Unand Hospital on health workers, doctor job satisfaction is lower than other health workers. Low job satisfaction among doctors can cause a decrease in hospital service quality. The purpose of this research is to analyze the factors related to the job satisfaction of doctors during the Covid-19 pandemic. The research method used is the quantitative method. Dependent variable in this study is overall job satisfaction, the independent variables are salary, promotion, fringe benefit, supervision, contingent reward, operating conditions, co-workers, nature of work, and communication. The sampling using census conducted on all doctors at Unand Hospital, where 71 doctors met the inclusion criteria. Data was collected by distributing job satisfaction survey (JSS) questionnaires. Univariate and bivariate analysis was used in this study. The result of this study is salary, fringe benefits, and operating procedure has the lowest average of the nine factors of job satisfaction, hospital management should pay attention for this aspect to maintain doctor job satisfaction.